Improving the understanding of and methods for the detection of fungal wheat pathogens - Roberts, Emily May (2018)
Wheat is a staple food for 35% of the world’s population providing roughly 20% of its calorific and 25% of its protein intake. Puccinia triticina, Zymoseptoria tritici and Fusarium graminearum are some of the most economically damaging fungi causing huge wheat yield losses. Problems that arise when trying to manage fungal pathogens include: the ability of fungal species to quickly adapt and overcome resistant cultivars of wheat, the overuse of fungicides leading to a high selection pressure for pathogen resistance and early detection often being dependent upon the experience and skill of the observer. This thesis focuses on developing detection methods which highlight the need for an integrated approach to disease management. In this study a specific monoclonal antibody, 29.G7.A9, was developed for early detection of Fusarium graminearum macroconidia spores. Immunofluorescence demonstrated the ability of this antibody to bind to the native protein in F. graminearum spores. The 29.G7.A9 antibody was incorporated into a portable amperometric immunosensor system for spore detection using screen printed electrodes. A Z. tritici population from three farms was analysed for the prevalence and distribution of amino acid alterations in the CYP51 protein, as well as the presence of inserts in the putative CYP51 promoter region, resulting in two general potential targets for detecting azole resistance being proposed. A clustering effect was observed with certain variant types showing association to certain geographical locations i.e. farm, field, and areas within a field. For this reason a future sampling plan was suggested with different sampling options in order to optimise the detection of certain variant types that may occur within a population in a specific location. A method was established to quantitatively characterize the development of Z. tritici on wheat plants throughout a complete infection cycle as well as observe differences in disease progression when different doses of a fungicide (epoxiconazole) were applied. This thesis provides techniques and information for generating further research and contributing new ideas for a more integrated approach for fungal crop pathogen detection research.